A composite conductive paste and preparation method thereof
By combining nano-copper wires in nano-silver paste and combining epoxy resin and other materials, a composite conductive paste with high conductivity and good bending resistance is prepared, which solves the application of existing conductive silver paste in the field of screen repair. The problem of limitation has achieved a double improvement in conductivity and cost.
Patent Information
- Application Number
- CN202111663834.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-12-31
AI Technical Summary
The existing conductive silver paste is limited in the field of screen repair, and cannot meet the high requirements for conductivity, fluidity, smoothness and curing temperature, and is also at a high cost.
By compositeing nano-copper wires in nano-silver paste, a composite conductive paste with high conductivity and good bending resistance is prepared, and epoxy resin, thickener, leveling agent, dispersant and solvent are used as solvent carriers. , reduce curing temperature and production costs.
It realizes high conductivity, good adhesion and low cost of conductive paste, and is suitable for fine repair of ITO film wire breaks, reducing the cost of screen repair and resource utilization difficulty.
Smart Images

Figure CN114283965B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive paste preparation, and in particular relates to a composite conductive paste and a preparation method thereof. Background Art
[0002] The popularity of mobile phones, computers, televisions and various smart devices has brought a huge market to screen manufacturers such as capacitive screens and resistive screens, and has also greatly driven the screen repair market. Screen repair is mainly due to damage to the electronic components and connection lines in the screen. Conductive paste is a key material for packaging, electrodes and interconnections of electronic components in the screen. Existing conductive pastes have been widely used in the fields of touch screen electric field circuits and membrane button settings. However, judging from the current application situation, the application of conductive paste in the screen repair market is relatively limited.
[0003] Conductive silver paste on the market is suitable for large-area one-time molding circuit settings, and the requirements for the fluidity, smoothness, curing temperature, etc. of the conductive paste are relatively low. However, for the field of screen repair, it is necessary to consider the subtlety of screen defects and the impact of repair conditions on other intact components in the screen, so it is necessary to use conductive paste with a finer structure, better conductivity, and looser requirements for the use environment. At the same time, since screen repair itself has considerations for cost and resource utilization, it is also crucial to reduce the cost of repair materials. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a composite conductive paste and a preparation method thereof. By compounding nano-copper wires in nano-silver paste, the prepared composite conductive paste has high conductivity, good bending resistance and high process stability, and low cost, and is suitable for repairing broken ITO films of liquid crystal screens.
[0005] In a first aspect, the present invention provides a composite conductive paste, comprising a functional material and a solvent carrier, wherein the functional material is added in an amount of 30-50% and the solvent carrier is added in an amount of 50-70% based on the total mass of the composite conductive paste as 100%;
[0006] Wherein, the functional material comprises nano silver wires with an addition amount of 10-20% and nano copper wires with an addition amount of 20-30%; preferably, the functional material comprises nano silver wires with an addition amount of 15% and nano copper wires with an addition amount of 25%.
[0007] Furthermore, the average wire diameters of the silver nanowires and the copper nanowires are both 20-50 nm.
[0008] The present invention uses nano silver wires and nano copper wires as conductive functional materials. The linear nano silver and nano copper can overlap each other to form a network-like conductive system, thereby avoiding the problem of weak conductivity of the conventional conductive paste due to the use of nano silver particles. Moreover, the selected conductive silver wires and conductive copper wires are both nano-grade materials with an average wire diameter of only 20-50 nm, which can ensure good conductivity under a narrow printing line width and is suitable for repairing small defects. Furthermore, compared with the conventional single conductive silver paste, the present invention replaces part of the conductive material nano silver with nano copper, which, on the one hand, greatly reduces the preparation cost of the conductive paste, and on the other hand, because the nano copper wire also has good conductivity, the conductive performance of the conductive paste will not be lost.
[0009] Further, the solvent carrier includes an epoxy resin added in an amount of 30-40%, a thickener added in an amount of 1-5%, a leveling agent added in an amount of 0.5-2%, a dispersant added in an amount of 0.1-1% and a solvent added in an amount of 10-20%; preferably, the solvent carrier includes an epoxy resin added in an amount of 35%, a thickener added in an amount of 3%, a leveling agent added in an amount of 1%, a dispersant added in an amount of 0.5% and a solvent added in an amount of 15%.
[0010] Specifically, the epoxy resin is 4-epoxycyclohexyl methyl ester; the thickener is selected from at least one of hydroxypropyl methylcellulose, methyl cellulose, and polyethylene glycol; the leveling agent is methyl acrylate; the dispersant is selected from at least one of polycarboxylates, polyvinyl alcohol, and n-butanol; and the solvent is selected from at least one of ethylene glycol and ethanol.
[0011] Epoxy resin has low shrinkage rate after curing, good weather resistance, excellent flexibility and wear resistance, and can effectively adhere to the surface of the substrate, thereby improving the adhesion and contact performance of the conductive paste to the ITO film or liquid crystal screen; the thickener is used to ensure the viscosity of the conductive paste to adapt to various coating methods such as scraping and spin coating; the leveling agent is used to improve the brush marks when the conductive paste is brushed, avoid defects such as pinholes and shrinkage holes during the curing process, and improve the surface quality; the dispersant is used to prevent the conductive paste from flocculation and agglomeration, so that the dispersed system is in a stable state and is conducive to preservation; ethanol with a defoaming effect is selected as a solvent to eliminate bubbles formed by the surfactant in the solvent carrier during the production process due to stirring, grinding and other operations that draw air, thereby avoiding bubbles affecting the dispersion of nano silver wires and nano copper wires in the conductive paste and improving the uniformity of the conductive paste.
[0012] In a second aspect, the present invention further provides a method for preparing the composite conductive paste as described above, comprising the following steps:
[0013] Step (1) Preparation of silver nanowires:
[0014] Mix silver nitrate ethylene glycol solution, potassium chloride ethylene glycol solution and polyvinyl pyrrolidone ethylene glycol solution, add dimethylacetamide, stir evenly, heat at 110-180°C for 4-12h, cool the product, centrifuge, wash and filter, and obtain nano silver wires;
[0015] Step (2) Preparation of nano copper wires:
[0016] Mix the glucose aqueous solution and the copper chloride ethanol solution, add oleylamine, stir evenly, heat at 100-150°C for 8-12h, cool the product, centrifuge, wash and filter, and obtain nano copper wires;
[0017] Step (3) Preparation of conductive paste:
[0018] 1) fully mixing a thickener, a leveling agent, a dispersant and a solvent to obtain a mixed solvent;
[0019] 2) adding epoxy resin to the mixed solvent and stirring evenly to obtain a solvent carrier;
[0020] 3) Adding the nano silver wires obtained in step (1) and the nano copper wires obtained in step (2) into the solvent carrier to obtain a conductive silver paste.
[0021] Furthermore, the concentration of the silver nitrate ethylene glycol solution in step (1) is 0.01-0.05 mol / L, and the molar ratio of potassium chloride in the potassium chloride ethylene glycol solution to silver nitrate in the silver nitrate ethylene glycol solution is 1:10-1:1000.
[0022] Furthermore, the molar ratio of polyvinyl pyrrolidone in the polyvinyl pyrrolidone glycol solution to silver nitrate in the silver nitrate glycol solution is 1:1-10:1, and the volume ratio of dimethylacetamide to the total ethylene glycol in the silver nitrate glycol solution, potassium chloride glycol solution, and polyvinyl pyrrolidone glycol solution is 1:10-1:50. The molecular weight of the polyvinyl pyrrolidone is 8000-56000.
[0023] Furthermore, the concentration of the copper chloride ethanol solution in step (2) is 0.01-0.1 mol / L, and the molar ratio of glucose in the glucose aqueous solution to copper chloride in the copper chloride ethanol solution is 1:1-5:1.
[0024] Furthermore, the molar ratio of the oleylamine to the copper chloride in the copper chloride ethanol solution is 2:1-10:1.
[0025] Furthermore, in step (3), the step of "adding epoxy resin to the mixed solvent and stirring evenly to obtain a solvent carrier" has a stirring speed of 100 r / min, a stirring time of 1 h, and a stirring temperature of 80°C.
[0026] Furthermore, in step (3), the step of "adding the silver nanowires obtained in step (1) and the copper nanowires obtained in step (2) to the solvent carrier and stirring evenly to obtain a conductive slurry" has a stirring speed of 200 r / min and a stirring time of 1 h.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The composite conductive paste of the present invention comprises functional materials and solvent carriers, wherein the functional materials are nano-scale silver wire and copper wire conductive materials, which can effectively match small defects, control line width, and are suitable for fine repair of ITO film breakage; nano silver wire has excellent conductivity and flexibility, and adding nano copper wire with the same specific gravity further increases the conductive contact area of the functional material, which can effectively reduce the material cost while ensuring conductivity.
[0029] 2. Epoxy resin, thickener, leveling agent, dispersant, and solvent are added to the solvent carrier of the composite conductive paste of the present invention. The components work synergistically to enable the conductive paste to achieve low-temperature curing, and the curing temperature can be reduced to 40°C, while effectively improving the dispersibility and adhesion of the conductive paste.
[0030] 3. The preparation method of the composite conductive paste of the present invention is to mix, grind and sieve the functional material and the solvent carrier to obtain the composite conductive paste. The preparation process is simple, the production cost is low, and it is easy to implement, and it has good promotion and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a SEM image of the silver nanowires prepared in Example;
[0033] Figure 2 This is a SEM image of the nano copper wire prepared in Example;
[0034] Figure 3 It is a screen disconnection diagram;
[0035] Figure 4This is a printed line width diagram of the composite conductive paste prepared in Example 1 of the present application;
[0036] Figure 5 This is a diagram showing the repair effect after using the composite conductive paste prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.
[0038] Example 1
[0039] Step (1) Preparation of silver nanowires:
[0040] 100mL 0.05mol / L silver nitrate ethylene glycol solution, 10mL 0.05mol / L potassium chloride ethylene glycol solution, 100mL 0.05mol / L PVP ethylene glycol solution (wherein the molecular weight of PVP is 20000) were mixed, 10mL DMAC was added, stirred evenly at room temperature, heated to 150°C, and reacted for 8h; the reaction solution was cooled to room temperature, diluted 5 times with ethanol, centrifuged for 10min, the supernatant was removed, washed with acetone, and filtered to obtain nano silver wires with an average wire diameter of 30nm. Its SEM characterization picture is as shown below Figure 1 As shown;
[0041] Step (2) Preparation of nano copper wires:
[0042] 100 mL of 0.05 mol / L glucose aqueous solution and 100 mL of 0.05 mol / L copper chloride ethanol solution were mixed and stirred evenly, 30 mmol / L of oleylamine was added, and the mixture was reacted at 120°C for 10 h. The reaction solution was cooled to room temperature, diluted with ethanol, centrifuged for 10 min, the supernatant was removed, washed with acetone, and filtered through a filter to obtain nano-copper wires with a diameter of 30 nm. The SEM characterization diagram is shown in FIG. Figure 2 As shown;
[0043] Step (3) Preparation of conductive paste:
[0044] 1) Take 20g of ethanol as a solvent and add it into a reaction kettle, add 2.5g of polyethylene glycol, 1g of methyl acrylate, and 0.5g of polyvinyl alcohol, keep the temperature at 60°C and stir for 30 minutes, then mix well to obtain a solvent mixture.
[0045] 2) Add 35 g of 4-epoxycyclohexyl methyl ester to the mixed solvent, raise the temperature to 80° C., adjust the stirrer speed to 100 r / min, and stir thoroughly for 1 hour to fully mix the resin to obtain a solvent carrier.
[0046] 3) 15 g of the nano silver wire obtained in step (1) and 25 g of the nano copper wire obtained in step (2) were added to a solvent carrier, the stirrer speed was adjusted to 200 r / min, and the mixture was stirred for 1 h. The mixture was introduced into a three-roll grinder for grinding and dispersion, and finally filtered through a 1000-mesh sieve to obtain the desired composite conductive slurry.
[0047] Example 2
[0048] Step (1) Preparation of silver nanowires:
[0049] 50 mL of 0.03 mol / L silver nitrate ethylene glycol solution, 4 mL of 0.03 mol / L potassium chloride ethylene glycol solution, and 200 mL of 0.03 mol / L PVP ethylene glycol solution (wherein the molecular weight of PVP is 10000) were mixed, 10 mL of DMAC was added, stirred evenly at room temperature, heated to 150°C, and reacted for 8 hours; the reaction solution was cooled to room temperature, diluted 5 times with ethanol, centrifuged for 10 minutes, the supernatant was removed, washed with acetone, and filtered to obtain nano silver wires with a diameter of 25 nm;
[0050] Step (2) Preparation of nano copper wires:
[0051] 50 mL of 0.03 mol / L glucose aqueous solution and 10 mL of 0.03 mol / L copper chloride ethanol solution were mixed and stirred evenly, 3 mmol of oleylamine was added, and the mixture was reacted at 150°C for 8 h; the reaction solution was cooled to room temperature, diluted with ethanol, centrifuged for 10 min, the supernatant was removed, washed with acetone, and filtered to obtain nano copper wires with a diameter of 28 nm;
[0052] Step (3) Preparation of conductive paste:
[0053] 1) Take 10g of ethylene glycol as a solvent and add it into a reaction kettle, add 5g of methyl cellulose, 2g of leveling agent methyl acrylate, and 1g of n-butanol, keep the temperature at 60°C and stir for 30 minutes, then mix evenly to obtain a solvent mixture.
[0054] 2) Add 40 g of 4-epoxycyclohexyl methyl ester to the mixed solvent, raise the temperature to 80° C., adjust the stirrer speed to 100 r / min, and stir thoroughly for 1 hour to fully mix the resin to obtain a solvent carrier.
[0055] 3) Add 20 g of the nano silver wire obtained in step (1) and 20 g of the nano copper wire obtained in step (2) into a solvent carrier, adjust the stirrer speed to 200 r / min, stir thoroughly for 1 h, introduce into a three-roll grinder for grinding and dispersion, and finally filter with a 1000-mesh sieve to obtain the desired composite conductive slurry.
[0056] Example 3
[0057] Step (1) Preparation of silver nanowires:
[0058] 100 mL of 0.01 mol / L silver nitrate ethylene glycol solution, 1 mL of 0.01 mol / L potassium chloride ethylene glycol solution, and 800 mL of 0.01 mol / L PVP ethylene glycol solution (wherein the molecular weight of PVP is 50,000) were mixed, and 20 mL of DMAC was added, and stirred evenly at room temperature, heated to 180°C, and reacted for 4 hours; the reaction solution was cooled to room temperature, diluted 5 times with ethanol, centrifuged for 10 minutes, the supernatant was removed, washed with acetone, and filtered through a filter to obtain nano silver wires with a diameter of 45 nm;
[0059] Step (2) Preparation of nano copper wires:
[0060] 10 mL of 0.1 mol / L glucose aqueous solution and 2 mL of 0.1 mol / L copper chloride ethanol solution were mixed and stirred evenly, 10 mmoL of oleylamine was added, and the mixture was reacted at 100°C for 12 h; the reaction solution was cooled to room temperature, diluted with ethanol, centrifuged for 10 min, the supernatant was removed, washed with acetone, and filtered to obtain nano copper wires with a diameter of 40 nm;
[0061] Step (3) Preparation of conductive paste:
[0062] 1) Take 20g of ethanol as a solvent and add it into a reaction kettle, add 1g of hydroxypropyl methylcellulose, 1g of methyl acrylate, and 0.5g of polyvinyl alcohol, keep the temperature at 60°C and stir for 30 minutes, then mix evenly to obtain a solvent mixture.
[0063] 2) Add 30 g of 4-epoxycyclohexyl methyl ester to the mixed solvent, raise the temperature to 80° C., adjust the stirrer speed to 100 r / min, and stir thoroughly for 1 hour to fully mix the resin to obtain a solvent carrier.
[0064] 3) 10 g of the silver nanowires obtained in step (1) and 30 g of the copper nanowires obtained in step (2) were added to a solvent carrier, the stirrer speed was adjusted to 200 r / min, the mixture was stirred for 1 h, and the mixture was introduced into a three-roll mill for grinding and dispersion. Finally, the mixture was filtered through a 1000-mesh sieve to obtain the desired composite conductive slurry.
[0065] Comparative Example 1
[0066] This comparative example includes most of the operating steps of Example 1, except that:
[0067] Step (2) is not included and the raw materials of step (3) do not contain nano copper wires.
[0068] Comparative Example 2
[0069] This comparative example includes most of the operating steps of Example 1, except that:
[0070] In step (3), 15 g of the silver nanowires obtained in step (1) and 50 g of the copper nanowires obtained in step (2) were added.
[0071] Comparative Example 3
[0072] This comparative example includes most of the operating steps of Example 1, except that:
[0073] In step (3), 15 g of the silver nanowires obtained in step (1) and 5 g of the copper nanowires obtained in step (2) were added.
[0074] Comparative Example 4
[0075] This comparative example includes most of the operating steps of Example 1, except that:
[0076] In step (3), 5 g of the silver nanowires obtained in step (1) and 25 g of the copper nanowires obtained in step (2) were added.
[0077] Comparative Example 5
[0078] This comparative example includes most of the operating steps of Example 1, except that:
[0079] In step (3), 50 g of the silver nanowires obtained in step (1) and 25 g of the copper nanowires obtained in step (2) are added.
[0080] Comparative Example 6
[0081] This comparative example includes most of the operating steps of Example 1, except that:
[0082] The method does not contain step (1) and step (2), and the diameters of the silver nanowires and the copper nanowires in step (3) are both 10 nm.
[0083] Comparative Example 7
[0084] This comparative example includes most of the operating steps of Example 1, except that:
[0085] The method does not contain step (1) and step (2), and the diameters of the nano silver wires and nano copper wires in step (3) are both 80 nm.
[0086] Comparative Example 8
[0087] This comparative example includes most of the operating steps of Example 1, except that:
[0088] The method does not contain step (1) and step (2), and in step (3), the diameter of the silver nanowire is 30 nm, and the diameter of the copper nanowire is 80 nm.
[0089] Comparative Example 9
[0090] This comparative example includes most of the operating steps of Example 1, except that:
[0091] The method does not contain step (1) and step (2), and in step (3), the diameter of the silver nanowire is 80 nm, and the diameter of the copper nanowire is 30 nm.
[0092] Comparative Example 10
[0093] Step (1) Preparation of silver nanowires:
[0094] 100 mL of 0.05 mol / L silver nitrate ethylene glycol solution, 10 mL of 0.05 mol / L potassium chloride ethylene glycol solution, and 100 mL of 0.05 mol / L PVP ethylene glycol solution (wherein the molecular weight of PVP is 20,000) were mixed, 10 mL of DMAC was added, stirred evenly at room temperature, heated to 150°C, and reacted for 8 hours; the reaction solution was cooled to room temperature, diluted 5 times with ethanol, centrifuged for 10 minutes, the supernatant was removed, washed with acetone, and filtered to obtain nano silver wires;
[0095] Step (2) Preparation of nano copper wires:
[0096] 100 mL of 0.05 mol / L glucose aqueous solution and 100 mL of 0.05 mol / L copper chloride ethanol solution were mixed and stirred evenly, 30 mmol / L of oleylamine was added, and the mixture was reacted at 120°C for 10 h; the reaction solution was cooled to room temperature, diluted with ethanol, centrifuged for 10 min, the supernatant was removed, washed with acetone, and filtered to obtain nano copper wires;
[0097] Step (3) Preparation of conductive paste:
[0098] 1) Take 20 g of ethanol as a solvent and add it into a reaction kettle, add 2.5 g of polyethylene glycol, 1 g of methyl acrylate, and 0.5 g of polyvinyl alcohol, stir at room temperature for 0.5 h, and mix well to obtain a solvent mixture.
[0099] 2) Add 35 g of 4-epoxycyclohexyl methyl ester to the mixed solvent, adjust the stirrer speed to 100 r / min, and stir thoroughly for 0.5 h at room temperature to fully mix the resin to obtain a solvent carrier.
[0100] 3) 15 g of the nano silver wire obtained in step (1) and 25 g of the nano copper wire obtained in step (2) were added to a solvent carrier, the stirrer speed was adjusted to 100 r / min, and the mixture was stirred for 0.5 h. The mixture was introduced into a three-roll grinder for grinding and dispersion, and finally filtered through a 1000-mesh sieve to obtain the desired composite conductive slurry.
[0101] 1. The performance of the conductive pastes prepared in the above Examples 1-3 and Comparative Examples 1-10 was tested, and the test data are recorded in Table 1.
[0102] Table 1
[0103]
[0104] It can be seen from the test data in Table 1 that the composite conductive paste prepared in Examples 1-3 of the present application has good conductive properties, with a resistance of only 4.8-5.2 (μΩ·cm). It can be seen that the conductive material in the conductive paste is well dispersed and the conductive density is high; and the composite conductive paste can be cured at a relatively low temperature of 40°C, and the curing time is only 1 minute, which effectively avoids the damage to the screen components caused by the high-temperature curing required for conventional conductive pastes, and realizes rapid repair at the same time; the composite conductive paste of the present application has good adhesion to materials, good tolerance to solvents, and good conductivity, which can well meet the needs of screen rework.
[0105] Comparative Example 1 is a single conductive silver paste without adding nano copper wires. Under the same conditions, if fine repairs are to be made to small defects on the screen, the silver content of the conductive silver paste needs to be greatly increased, otherwise good conductivity cannot be guaranteed, and increasing the amount of nano silver will lead to a significant increase in cost; Comparative Examples 2-3 are discussions on the content of nano copper wires. When the content of nano copper wires increases to a limited value, the electrical performance is no longer improved, and the cost increases. In addition, if the content of nano copper wires is too high, the probability of being coated by the bonding resin is low, and its adhesion decreases after curing, and it is easy to fall off; when the content of nano copper wires is too low, good conductivity cannot be achieved; Comparative Examples 4-5 are discussions on the content of nano silver wires. If the content of nano silver wires is too high, the cost will increase, and if the content is too low, the conductivity will be poor.
[0106] Comparative Examples 6-9 are experiments on the selection of wire diameters of nanosilver wires and nanocopper wires in a composite conductive paste. From the test data in Table 1, it can be seen that when the wire diameter is larger, the dispersibility is poor, and the effective contact area of nanosilver wires and nanocopper wires of the same order of magnitude becomes smaller, and the conductive performance is weaker; when the wire diameter is smaller, the difficulty of preparation increases, resulting in increased costs.
[0107] Comparative Example 10 is a discussion on the setting of relevant parameters in the preparation process of the composite conductive paste. Insufficient stirring time and too low temperature in the preparation process will affect the dispersibility of the conductive paste and reduce its conductive performance.
[0108] 2. Screen repair test using the composite conductive paste prepared in Example 1
[0109] The composite conductive paste prepared in Example 1 is adhered to the defective part of the ITO conductive path in the form of printing paste and then cured.
[0110] Figure 3-5 They are screen break diagram, composite conductive paste printing line width diagram, and break repair diagram.
[0111] from Figure 3 It can be seen that the line width of the screen laser etching line is only 60μm. In order to avoid the short circuit between laser lines caused by the excessive line width of the repair line during the repair process, the line width of the conductive paste printing must be less than this value. Figure 4 It can be seen that the line width of the conductor printed by the composite conductive paste of the present invention is 50 μm, which meets the repair requirements; Figure 5 This is a picture showing the effect after repair. It can be seen that the broken screen line is completely repaired by using the composite conductive paste of the present invention.
[0112] In summary, the composite conductive paste prepared in the present application has good conductivity, good adhesion to materials, and greatly reduced cost. In practical applications, it can better repair screen defects and has good application value.
[0113] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A composite conductive paste for screen repair, characterized in that: Comprising a functional material and a solvent carrier, based on the total mass of the composite conductive paste for screen repair being 100%, the added amount of the functional material is 30-50%, and the added amount of the solvent carrier is 50-70%; Wherein, the functional material includes nano silver wires with an addition amount of 10-20% and nano copper wires with an addition amount of 20-30%; The average wire diameters of the silver nanowires and the copper nanowires are both 20-50 nm; The solvent carrier comprises 30-40% of epoxy resin, 1-5% of thickener, 0.5-2% of leveling agent, 0.1-1% of dispersant and 10-20% of solvent.
2. A method for preparing the composite conductive paste for screen repair according to claim 1, characterized in that: The following steps are involved: Step (1) Preparation of silver nanowires: Mixing silver nitrate ethylene glycol solution, potassium chloride ethylene glycol solution and polyvinyl pyrrolidone ethylene glycol solution, adding dimethylacetamide and heating to react, thereby obtaining nano silver wires; Step (2) Preparation of nano copper wires: Mixing a glucose aqueous solution and a copper chloride ethanol solution, adding oleylamine and heating to react, thereby obtaining nano copper wires; Step (3) Preparation of conductive paste: 1) fully mixing a thickener, a leveling agent, a dispersant and a solvent to obtain a mixed solvent; 2) adding epoxy resin to the mixed solvent and stirring evenly to obtain a solvent carrier; 3) Adding the nano silver wires obtained in step (1) and the nano copper wires obtained in step (2) into the solvent carrier, stirring evenly, to obtain a conductive paste.
3. The method for preparing the composite conductive paste for screen repair according to claim 2, characterized in that: The concentration of the silver nitrate ethylene glycol solution in step (1) is 0.01-0.05 mol / L, and the molar ratio of potassium chloride in the potassium chloride ethylene glycol solution to silver nitrate in the silver nitrate ethylene glycol solution is 1:10-1:1000.
4. The method for preparing the composite conductive paste for screen repair according to claim 2, characterized in that: The molar ratio of polyvinyl pyrrolidone in the polyvinyl pyrrolidone glycol solution to silver nitrate in the silver nitrate glycol solution is 1:1-10:1, and the volume ratio of dimethylacetamide to the total ethylene glycol in the silver nitrate glycol solution, potassium chloride glycol solution and polyvinyl pyrrolidone glycol solution is 1:10-1:
50.
5. The method for preparing the composite conductive paste for screen repair according to claim 2, characterized in that: The concentration of the copper chloride ethanol solution in step (2) is 0.01-0.1 mol / L, and the molar ratio of glucose in the glucose aqueous solution to copper chloride in the copper chloride ethanol solution is 1:1-5:
1.
6. The method for preparing the composite conductive paste for screen repair according to claim 2, characterized in that: The molar ratio of the oleylamine to the copper chloride in the copper chloride ethanol solution is 2:1-10:
1.
7. The method for preparing the composite conductive paste for screen repair according to claim 2, characterized in that: In step (3), the step of "adding epoxy resin to the mixed solvent and stirring evenly to obtain a solvent carrier" has a stirring speed of 100 r / min, a stirring time of 1 h, and a stirring temperature of 80°C.
8. The method for preparing the composite conductive paste for screen repair according to claim 2, characterized in that: In step (3), the step of "adding the silver nanowires obtained in step (1) and the copper nanowires obtained in step (2) to the solvent carrier and stirring evenly to obtain a conductive slurry" has a stirring speed of 200 r / min and a stirring time of 1 h.
Citation Information
Patent Citations
Manufacturing method for nanometal transparent conductive film
CN103996455A
Multilayer anisotropic conductive film containing nanowires
CN106413250A
Nano conductive silver paste, and preparation method and application thereof
CN110534228A
Conductive paste, preparation method and display device comprising conductive paste
CN110890167A